2011
DOI: 10.1002/ibd.21608
|View full text |Cite
|
Sign up to set email alerts
|

Associations between variants in the ABCB1 (MDR1) gene and corticosteroid dependence in children with Crohnʼs disease

Abstract: Our results suggest that the ABCB1 gene may be associated with CS dependence in pediatric CD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 57 publications
3
12
0
Order By: Relevance
“…In the present study, we report positive associations between the C3435T polymorphism and both the chronic use of steroids and disease activity in CD patients. Similar to our results, an association between MDR1 variants and corticosteroid dependence was also reported in children with CD in Canadian tertiary centers (37). In a British study on IBD, the 2677T allele was increased in UC cases, and the TT genotype was strongly associated with disease severity and the use of steroids in UC (27).…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, we report positive associations between the C3435T polymorphism and both the chronic use of steroids and disease activity in CD patients. Similar to our results, an association between MDR1 variants and corticosteroid dependence was also reported in children with CD in Canadian tertiary centers (37). In a British study on IBD, the 2677T allele was increased in UC cases, and the TT genotype was strongly associated with disease severity and the use of steroids in UC (27).…”
Section: Discussionsupporting
confidence: 91%
“…We have found no connection between the method of GC therapy and response to it. The GC drugs used in our studies were similar to those investigated in earlier pharmacogenetic research on patients with IBD conducted by Krupoves et al, who evaluated prednisolone and budesonide [24,25]. Gender also showed no effect on the response to the GCs, but we did identify a significant difference in treatment between patients with CD and UC.…”
Section: Discussionsupporting
confidence: 76%
“…The wild genotype CC of rs1128503 (C1236T) and rs1045642 (C3435T) should be regarded as risk factors for GC‐dependence in the Chinese CD population. In a previous study, Krupoves et al . included 260 pediatric CD patients and found that rs1045642 (C3435T) was not correlated with GC sensitivity.…”
Section: Discussionmentioning
confidence: 79%